Sapogenin content variation in Medicago inter‐specific hybrid derivatives highlights some aspects of saponin synthesis and control. Issue 1 (18th November 2014) - Carelli, Maria; Biazzi, Elisa; Tava, Aldo; Losini, Ilaria; Abbruscato, Pamela; Depedro, Claudia; Scotti, Carla
Summary In the Medicago genus, saponins are a complex mixture of triterpene glycosides showing a broad spectrum of biological properties. Here we analyzed the variation in the sapogenin content and composition of inter‐specific hybrid Medicago sativa × Medicago arborea derivatives to highlight the pattern of this variation in plant organs (leaves/roots) and the possible mechanisms underlying it. In Sativa Arborea Cross (SAC) leaves and roots, saponins and sapogenins were evaluated using chromatographic methods. Phenotypic correlations between sapogenin content and bio‐agronomic traits were examined. Expression studies on β‐amyrin synthase and four cytochromes P450 (CYPs) involved in sapogenin biosynthesis and sequence analysis of the key gene of the hemolytic sapogenin pathway (CYP716A12) were performed. Chromatographic analyses revealed a different pattern of among‐family variation for hemolytic and nonhemolytic sapogenins and saponins and for the two organs/tissues. Different correlation patterns of gene expression in roots and leaves were found. Diachronic analysis revealed a relationship between sapogenin content and gene transcriptional levels in the early stages of the productive cycle. The results suggest that there are different control mechanisms acting on sapogenin biosynthesis for leaves and roots, which are discussed. A key role for medicagenic acid in the control of sapogenin content in both the tissues is proposed and discussed.